2024
DOI: 10.1002/lpor.202301388
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dot‐Doped Optical Fibers

Zixuan Zhu,
Siqi Sun,
Xiaomei Chai
et al.

Abstract: Gain medium‐doped active optical fibers for optical amplification and long‐range transmission have triggered a lot of researches. Traditional rare‐earth ion‐doped active fibers have non‐adjustable emissions, narrow band luminescence, limited gain enhancement, and other challenges. The unique optical properties of quantum dots (QDs) can further improve the doped optical fibers in the light amplification capacity, temperature sensitivity and to gain a broad‐spectrum coverage and lower laser threshold and other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 161 publications
0
0
0
Order By: Relevance
“…Light/lasers with wavelengths of 632.8 and 1550 nm are broadly utilized in a wide range of fields; , we thus selected the n values of the polymer films at these two wavelengths to describe the light refractive properties. As expected, the results in Figure A demonstrated that all SFH polymers possessed high n values in a wide wavelength range with much higher n values at 632.8 nm ( n 632.8 ) than those of the commercially important optical plastics ( n = ∼1.49–1.59) .…”
Section: Resultsmentioning
confidence: 99%
“…Light/lasers with wavelengths of 632.8 and 1550 nm are broadly utilized in a wide range of fields; , we thus selected the n values of the polymer films at these two wavelengths to describe the light refractive properties. As expected, the results in Figure A demonstrated that all SFH polymers possessed high n values in a wide wavelength range with much higher n values at 632.8 nm ( n 632.8 ) than those of the commercially important optical plastics ( n = ∼1.49–1.59) .…”
Section: Resultsmentioning
confidence: 99%